2011
DOI: 10.3346/jkms.2011.26.5.637
|View full text |Cite
|
Sign up to set email alerts
|

Time Trend and Age-Period-Cohort Effects on Acute Myocardial Infarction Mortality in Korean Adults from 1988 to 2007

Abstract: We examined time trend and age-period-cohort effects on acute myocardial infarction (AMI) mortality in Korean adults from 1988 to 2007. Annual AMI mortality data and population statistics from 1988 to 2007 were obtained from the STATISTICS KOREA website. Age adjusted mortality for four 5-yr calendar periods (1988-1992 to 2003-2007) was calculated by direct standardization using the Year 2000 WHO world standard population. A log-linear Poisson regression model was used to estimate age, period, and cohort effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
2
11
1
Order By: Relevance
“…Our study is similar to many others in showing that the decline in IHD is mainly due to a cohort effect [25], [26], [27], [28], [29], [30], although there are exceptions, for example in Australia [31] and New Zealand [32]. However, almost all these studies relate to settings (Figure 1) where an epidemic of ischemic heart disease occurred in the mid 20 th century, and thus do not elucidate why the original epidemic occurred [33].…”
Section: Discussionsupporting
confidence: 91%
“…Our study is similar to many others in showing that the decline in IHD is mainly due to a cohort effect [25], [26], [27], [28], [29], [30], although there are exceptions, for example in Australia [31] and New Zealand [32]. However, almost all these studies relate to settings (Figure 1) where an epidemic of ischemic heart disease occurred in the mid 20 th century, and thus do not elucidate why the original epidemic occurred [33].…”
Section: Discussionsupporting
confidence: 91%
“…The standardized incidence rate of myocardial infarction in this study is high compared with a 30-year study in Japan that reported myocardial infarction incidence rates of 7.4 and 27 per 100 000 in 1979 and 2008 respectively (25). Our results are also higher compared with age-adjusted, standardized mortality rates due to myocardial infarction in Korea in 2003 and 2007 at 30.86 and 28.5 per 100 000 respectively (26). However, the incidence rate was lower compared with a study in Finland reporting myocardial infarction incidence rates in men and women of 738.8 and 292.9 per 100 000 individuals respectively in a population of 35-to 84-year-olds (9).…”
Section: Discussioncontrasting
confidence: 65%
“…A recent study carried out in Brazil evidenced a progressive increase in mortality due to acute myocardial infarction with age, with higher mortality in men when compared to women in all regions of the country and both genders 44 . The progressive increased mortality has also been found in several other studies, such as those carried out in countries like South Korea 45 , Japan 46 , China 47 and Australia 48 . As with age, the association between overweight and increased cardiovascular risk has substantial evidence in the literature.…”
Section: Discussionsupporting
confidence: 74%